2012
DOI: 10.1063/1.4770486
|View full text |Cite
|
Sign up to set email alerts
|

Annealing induced colossal magnetocapacitance and colossal magnetoresistance in In-doped CdCr2S4

Abstract: The correlation between colossal magnetocapacitance (CMC) and colossal magnetoresistance (CMR) in CdCr 2 S 4 system has been revealed. The CMC is induced in polycrystalline Cd 0.97 In 0.03 Cr 2 S 4 by annealing in cadmium vapor. At the same time, an insulator-metal transition and a concomitant CMR are observed near the Curie temperature. In contrast, after the same annealing treatment, CdCr 2 S 4 displays a typical semiconductor behavior and does not show magnetic field dependent dielectric and electric transp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…9 Recently, the conclusion of conductive artefact is further evidenced by Yang et al, both experimentally and theoretically. 10,11 As a result, the design or tuning of multi-functional materials for potential applications enables the necessity to clear what stands behind the novel phenomena observed.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, the conclusion of conductive artefact is further evidenced by Yang et al, both experimentally and theoretically. 10,11 As a result, the design or tuning of multi-functional materials for potential applications enables the necessity to clear what stands behind the novel phenomena observed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, synthetic routes for chalcospinel films mainly include a wet chemistry method and a multiple-step spin-coating method using nanocrystals . The reported wet chemistry methods for the growth of CdCr 2 S 4 films, such as chemical bath deposition and electrochemical deposition, result in the poor crystallinity and impurities. For multiple-step spin-coating method, the nanocrystal defects and capped organic ligands negatively influence the electrical properties of the films, and additional annealing results in inevitable grain boundary defects and sulfur deficiency . Precursors reported in the literature for the chemical synthesis of bulk CdCr 2 S 4 , including elemental Cd/Cr, CdS, Cr 2 S 3 , CdCl 2 , CrCl 3 , CdO, CrO 3 , and CdCr 2 S 4 powder, require elevated temperature for volatilization and reaction. ,, Thus, development of suitable cadmium and chromium precursors with sufficient volatility and stability for the growth of high-quality nanostructured CdCr 2 S 4 films by chemical methods is an important challenge and a bottleneck for development of chalcogenide-based spintronic/electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ferromagnetic semiconductive spinel compounds have been studied for potential candidates for semiconductor spintronic devices. [1][2][3][4][5] A great deal of experimental attention has been concentrated on the cubic spinel compound CdCr 2 S 4 . In 2005, Hemberger et al [1] reported that the cubic spinel CdCr 2 S 4 has relaxor-like dielectric properties and colossal magnetocapacitance.…”
Section: Introductionmentioning
confidence: 99%